Free-Standing Iridescent Films of Cellulose Nanocrystal Doped with Eu3+ and Tb3+ Ions for Photonic Applications - Sanches, Pedro H. L.; do Santos, Molíria V. [UNESP]; Barud, Hernane S.; Ribeiro, Sidney J. L. [UNESP]; Caiut, José Maurício A. (American Chemical Society (ACS), 2025)
The simultaneous integration of iridescence and light emission into a photonic material is an attractive proposal for designing novel optical devices. These properties could be controlled by the action of chiral nematic liquid crystals, and the self-assembly of cellulose nanocrystals is a smart methodology for the development of this new material. Herein, bacterial cellulose (BC) has been used as a cellulose source, mainly due to its biocompatibility, nontoxicity, and high purity. In this context, cellulose nanocrystals (CNCs), obtained by acid hydrolysis methodology, have received significant interest in the production of new optical materials due to their controllable chiral nematic self-organization. The work aims to obtain new iridescent films based on CNCs with adjustable cholesteric pitch, in the presence of lanthanide ions (Ln3+), specifically Eu3+ and Tb3+ ions, as a new platform for optical systems. The results from scanning electron microscopy (SEM) confirmed the chiral nematic structure of the CNC film, and it was corroborated by the Bragg diffraction band observed at specular reflectance analysis. In addition, the following methodology allows control of the cholesteric pitch. The luminescence results from the spectroscopic probe, Eu3+ ion, show the lanthanide in a low symmetry environment. The possibility of the shift of the Bragg band may influence Tb3+ ion emission, and as a result, the emission color changes. In conclusion, the ability to control the cholesteric pitch of the doped iridescent CNC films is associated with the angle-dependent excitation wavelength and consequently the emission of the material; these new films show an innovative path with potential applications in polarized luminescence and CNC-based optical devices, sensors, tunable filters, and lasers.